A numerical simulation of single bubble growth in subcooled boiling water. (February 2019) - Cheng, Ning; Guo, Yun; Peng, Changhong
Highlights: Bubble growth processes in subcooled boiling water have been numerically studied. The mass source has been modified to keep the liquid-vapor interface keep clear. The bubble contour and heat flow distribution fit the experimental results well. The temperature, velocity and mass source distribution have been presented. Abstract: Water-cooling blanket is closely related to system safety in future fusion reactor for it can cooling down the reactor. The process of cooling in water-cooling blanket may involve bubble generation under subcooled boiling condition. Although many researchers have investigated bubble generation numerically, the details of bubble generation in subcooled boiling remain unclear. In this paper a two-dimensional bubble growth simulation under subcooled nucleate boiling condition has been conducted using VOF (Volume of Fluid) method in ANSYS FLUENT. A phase change model was adopted by adding extra mass source term and energy source term to the Navier-Stokes equations in the cells adjacent to vapor-liquid interface. The variations of bubble contour before bubble departure, temperature fields, velocity fields and contribution of heat flux from superheated layer and subcooled fluid can be obtained by simulation. The results were compared with existing datum of visual experiment in previous literature to verify the validity of the simulation.